2022
DOI: 10.4240/wjgs.v14.i9.950
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of short-term efficacy between totally laparoscopic gastrectomy and laparoscopic assisted gastrectomy for elderly patients with gastric cancer

Abstract: BACKGROUND Totally laparoscopic gastrectomy (TLG) entails both gastrectomy and gastrointestinal reconstruction under laparoscopy. Compared with laparoscopic assisted gastrectomy (LAG), TLG has been demonstrated in many studies to require a smaller surgical incision, result in a faster postoperative recovery and less pain and have comparable long-term efficacy, which has been a research hotspot in recent years. Whether TLG is equally safe and feasible for elderly patients remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Li’s study also showed that MIG was a feasible and safe procedure for older patients, in contrast to MIG for nonolder patients and OG for older patients [ 7 ]. Moreover, our previous study revealed that MIG with intracorporeal anastomosis for older patients was safe and improved postoperative quality of life [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Li’s study also showed that MIG was a feasible and safe procedure for older patients, in contrast to MIG for nonolder patients and OG for older patients [ 7 ]. Moreover, our previous study revealed that MIG with intracorporeal anastomosis for older patients was safe and improved postoperative quality of life [ 8 ].…”
Section: Introductionmentioning
confidence: 99%